Myocardial Reloading After Extracorporeal Membrane Oxygenation Alters Substrate Metabolism While Promoting Protein Synthesis. Issue 4 (19th August 2013) - Kajimoto, Masaki; O'Kelly Priddy, Colleen M.; Ledee, Dolena R.; Xu, Chun; Isern, Nancy; Olson, Aaron K.; Rosiers, Christine Des; Portman, Michael A.
Abstract : Background: Extracorporeal membrane oxygenation (ECMO) unloads the heart, providing a bridge to recovery in children after myocardial stunning. ECMO also induces stress which can adversely affect the ability to reload or wean the heart from the circuit. Metabolic impairments induced by altered loading and/or stress conditions may impact weaning. However, cardiac substrate and amino acid requirements upon weaning are unknown. We assessed the hypothesis that ventricular reloading with ECMO modulates both substrate entry into the citric acid cycle (CAC) and myocardial protein synthesis. Methods and Results: Sixteen immature piglets (7.8 to 15.6 kg) were separated into 2 groups based on ventricular loading status: 8‐hour ECMO (UNLOAD) and postwean from ECMO (RELOAD). We infused into the coronary artery [2‐ 13 C]‐pyruvate as an oxidative substrate and [ 13 C6 ]‐L‐leucine as an indicator for amino acid oxidation and protein synthesis. Upon RELOAD, each functional parameter, which were decreased substantially by ECMO, recovered to near‐baseline level with the exclusion of minimum dP/dt. Accordingly, myocardial oxygen consumption was also increased, indicating that overall mitochondrial metabolism was reestablished. At the metabolic level, when compared to UNLOAD, RELOAD altered the contribution of various substrates/pathways to tissue pyruvate formation, favoring exogenous pyruvate versus glycolysis, and acetyl‐CoA formation, shifting away from pyruvate decarboxylation to endogenous substrate, presumably fatty acids. Furthermore, there was also a significant increase of tissue concentrations for all CAC intermediates (≈80%), suggesting enhanced anaplerosis, and of fractional protein synthesis rates (>70%). Conclusions: RELOAD alters both cytosolic and mitochondrial energy substrate metabolism, while favoring leucine incorporation into protein synthesis rather than oxidation in the CAC. Improved understanding of factors governing these metabolic perturbations may serve as a basis for interventions and thereby improve success rate from weaning from ECMO.